The Effect of Religiosity and Halal Labels on Purchasing of Muslim Consumer Purchases on Food and Halal Products in Packaging - Arwani, Agus; Maspupah, Maspupah (Khatulistiwa, 2021)
This study aims to determine the effect of religiosity and halal labels both partially and simultaneously on Muslim consumers' purchasing decisions on packaged foods and beverages. Muslim consumers should always consume all the good things that Allah SWT has provided on this earth to maintain our physical and spiritual qualities by consuming something that is lawful. This research method includes causal research with a quantitative approach. Data sources were obtained from primary data and secondary data, while the data in this study were obtained from observations, questionnaires, and documentation. In this study, there are independent variables namely religiosity (X1), halal label (X2) and purchasing decisions as the dependent variable (Y). The population of this study was Muslim consumers of women in the village of Jatingarang, Bodeh district, Pemalang district Center Java. The sampling technique uses a random sampling method to a sample of 95 respondents. The data analysis technique uses multiple linear regression techniques. The results showed (1) Religiosity significantly influence consumer purchase decisions Muslim in food and beverage products in containers with sig 0.001 0.05 or t value 3,568 t table 1.986 (2) The label kosher significantly influences consumer purchase decisions Muslim-on products packaged foods and drinks with sig values. 0.012 0.05 or the value of t count 2.560 t table 1.986 (3) based on the results of the F test, it is known that the two independent variables studied simultaneously influence the purchasing decisions of packaged food and beverage products indicated by F count of 13.106 F table 3.09 with a significance level of 0,000 0,05 (4) the adjusted R square value of 0,222, it shows that 22% of the purchase decision variables can be explained by the two independent variables, while the remaining 77,8% is influenced by other variables besides the two variables used in this research.